A Historical study of the Spiti Valley: Tracing the footprints of Tibetan Buddhism and its early dissemination (Bodhi Path, 2024)
The Spiti valley, situated in the south-western corner of the Tibetan Plateau, is known to scholars of Tibetan studies due to its close association with Rinchen Zangpo (Lochen Rinchen sZangpo) and its early history. Rinchen Zangpo initiated a significant campaign to spread Buddhism in western Tibet during the late 10th century, a period referred to as the "Second Diffusion of Buddhism" in Tibetan Buddhist history. Spiti, which was part of the newly established Guge Kingdom at that time, actively supported Rinchen Zangpo's endeavors by assisting in the construction of temples, monasteries, and other structures, as well as in the translation of Buddhist texts from Sanskrit to Tibetan. Among the key locations for these activities in Spiti was the ancient Tabo Monastery or Tabo Chos-Khor Monastery, which was built in 996 A.D.Research into the rich Buddhist heritage of Spiti and its connection to the "Second dissemination of Buddhism" has provided insight into the region during that period. However, there has been a lack of focus on Spiti's earlier history, leading to limited knowledge of its past until the 10th century. Notable intellectuals from the area, such as Angrup Lahauli and Dngos grup garsha pa, have emphasized that Spiti's history can be traced back to the 10th  century, with scarce reliable references to its earlier history in classical texts or inscriptions. Historians preceding my research have categorized the history of Spiti into three distinct phases. • A synthesis of four assumptions sourced from English, Hindi, and Tibetan references provides a logical framework for understanding the early history of Spiti, drawing on source documents and fieldwork.• As per the assertions in the sources, Spiti was under the rule of Hindu Sena monarchs during the 7th century, as documented by Hutchison & Vogel (1919; 1920a; 1933).• From the mid-seventh century to the mid-ninth century, Spiti operated under taxation system known as Khangchen, which mirrored the military administration structure of the preceding Tibetan Empire.
Keywords: Tibetan Buddhism; Spiti Valley